Integrating qualitative insights with large secondary data: a protocol for a community-engaged mixed-methods study on adolescent substance use - Silmi, Kazi Priyanka; Adkins-Jackson, Paris; Meléndrez, Blanca; Dang, Nghi; Zeray, Segen; Cardenas-Iniguez, Carlos; Pugh, Erika; Perez, Yailene; Cervantes, Nayeli; Peters, Precious; Hammonds, Stephanie; Covarrubias Reyna, Igdalia; et al. (Frontiers in Public Health, 2025)
Understanding the factors of risk and resilience for youth substance use requires interdisciplinary and multi-level methodological approaches that integrate the community of study into the research process. This protocol describes a novel, community-engaged, modified convergent mixed-methods design to investigate factors of neighborhood social risk and resilience (NSRR) in relation to substance use and neurocognition among Hispanic adolescents living in neighborhoods with unequal opportunities and restricted access to resources. We propose a design for integrating primary qualitative data with secondary data from the Adolescent Brain Cognitive Development (ABCD) Study, the largest longitudinal adolescent cohort in the United States. Guided by community-engaged research practices, and socio-ecological and health disparities frameworks, the protocol centers on the experience of young adolescents. Our design prioritizes partnerships among academic, community, and grassroots organizations to co-develop study design conceptualization, recruitment and analysis plan, along with the interpretation and dissemination of results. The secondary quantitative data analysis leverages advanced statistical modeling to examine relationships between neighborhood level factors and substance use, providing measurable insights both at the population level and at the neighborhood level. Qualitative interviews with adolescents provide an opportunity for collecting a rich, community-grounded perspective that captures the lived experience of adolescents in how neighborhood factors shape adolescent health behaviors. Findings will be synthesized using data integration and shared through academic, community-facing, and policy channels. This protocol highlights the importance of a community-engaged mixed-methods design that strengthens the cultural relevance, actionability, and validity of adolescent substance use research by embedding community voices throughout all phases of the research process.